2017
DOI: 10.1002/2017wr020567
|View full text |Cite
|
Sign up to set email alerts
|

Recent Extreme Runoff Observations From Coastal Arctic Watersheds in Alaska

Abstract: Arctic coastal watersheds, though rarely monitored, are expected to have increased runoff, as climate models predict more precipitation in the Arctic. This study provides a synthesis of streamflow changes in watersheds of the Alaska Arctic Coastal Plain (AACP) based on available historic discharge data and water balance analysis. A comparison of annual runoff from the Putuligayuk River watershed (471 km2) from the period 1970–1986 (78 ± 24.1 mm/yr) to the period 1999–2015 (122 ± 49.6 mm/yr) shows increasing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 64 publications
2
55
0
Order By: Relevance
“…An earlier start of freshet agrees with identified significant air temperature increases in May at 9 out of the 13 meteorological stations in the region. However, in contrast to the Lena River basin, where strong warming in spring led to an advance of the snowmelt season into late May and resulted in a lower daily maximum discharge in June (Yang et al, 2002;Tan et al, 2001), at the study gauges, streamflow has not been reduced in June (except ID 3510).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…An earlier start of freshet agrees with identified significant air temperature increases in May at 9 out of the 13 meteorological stations in the region. However, in contrast to the Lena River basin, where strong warming in spring led to an advance of the snowmelt season into late May and resulted in a lower daily maximum discharge in June (Yang et al, 2002;Tan et al, 2001), at the study gauges, streamflow has not been reduced in June (except ID 3510).…”
mentioning
confidence: 57%
“…Tananaev et al (2016) found that 30 small and medium-sized rivers out of 100 in the Lena River basin showed trends in mean annual flow. Significant changes have been recently reported for small and middle-sized rivers in northwestern Canada (Spence et al, 2011), Alaska (Stuefer et al, 2017), and the Canadian High Arctic (Lamoureux and Lafrenière, 2018) and attributed to climate change and permafrost disturbances. Further analysis of small river basins could reveal the mechanisms behind ongoing changes, as at larger scales attributing changes can be problematic.…”
Section: Introductionmentioning
confidence: 95%
“…Climate projections from Polar WRF show a wetting trend for the ACP, but with many extreme dry years interspersed (Figure 3). The summer drought of 2007 is prominent in the recent history of the Alaskan North Slope, resulting in a major tundra fire (Jones et al 2009c), shrinkage of lakes (Jones et al 2009a), and reduced river runoff and hydrologic connectivity (Arp et al 2012b;Betts and Kane 2015;Stuefer et al 2017).…”
Section: Scenarios Analysis To Address Uncertainty In Future Climate mentioning
confidence: 99%
“…At the same time as the industrial footprint has expanded on the ACP, climate change has become an increasing concern in the Arctic, with warming much above global trends (Serreze and Barry 2011;Wendler, Moore, and Galloway 2014). Ecosystem responses to climate change on Alaska's North Slope include earlier snowmelt (Stone et al 2002), shrubification (Sturm, Racine, and Tape 2001), permafrost warming Romanovsky, Smith, and Christiansen 2010) and degradation (Jorgenson, Shur, and Pullman 2006;Raynolds et al 2014;Liljedahl et al 2016), new tundra fires (Jones et al 2009c), accelerating coastal erosion (Jones et al 2009b), earlier breakup of lakes and rivers (Smejkalova, Edwards, and Dash 2017), and hydrologic intensification in the form of more variable watershed runoff (Rawlins et al 2010;Stuefer et al 2017). Climate-change impacts on native Inupiaq communities and the petroleum industry in northern Alaska are wide ranging with mixed consequences (Larsen et al 2008;Raynolds et al 2014;Brinkman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, EBS beluga would seem to be at lower risk of exposure than many marine mammal populations, due to the low density of human habitation (and presumably ownership of outdoor cats) in the region. However, it is important to note that coastal runoff is changing in the western Arctic of North America (Stuefer et al 2017). …”
Section: Risk Factors For Exposurementioning
confidence: 99%